1994
DOI: 10.1093/ije/23.5.940
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol Intake and Serum Lipids in a Japanese Population

Abstract: Alcohol drinkers have a higher HDL-cholesterol level and lower LDL-cholesterol level than non-drinkers. This anti-atherogenic lipid profile in alcohol drinkers may be explained by the effect of alcohol on serum lipids independent of age, BMI and smoking.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
37
1

Year Published

1998
1998
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(44 citation statements)
references
References 0 publications
6
37
1
Order By: Relevance
“…They also noticed that, after 2 weeks of alcohol abstinence, the HDL-C levels decreased to normal range. A study done by Choudhary et al found higher serum HDL-C in heavy alcohol drinkers [14]. However, in our study, there was no significant association observed between alcohol consumption and blood HDL level.…”
Section: Sahu Et Alcontrasting
confidence: 89%
“…They also noticed that, after 2 weeks of alcohol abstinence, the HDL-C levels decreased to normal range. A study done by Choudhary et al found higher serum HDL-C in heavy alcohol drinkers [14]. However, in our study, there was no significant association observed between alcohol consumption and blood HDL level.…”
Section: Sahu Et Alcontrasting
confidence: 89%
“…Potential mechanisms by which moderate ethanol intake might reduce the incidence of cardiovascular disease have previously been reported. 14,[26][27][28][29] Alcohol intake has been associated with elevated serum high-density lipoprotein (HDL) cholesterol, 14,26 as well as reductions in blood clotting factors, 27 platelet aggregation, 28 and insulin resistance. 29 Some studies have demonstrated a more beneficial effect for wine than for other alcoholic beverages.…”
Section: Discussionmentioning
confidence: 99%
“…This result is consistent with the results of other epidemiologic or metabolic studies concerning the effects of different types of alcoholic beverages on blood pressure 43 or lipids. 14,30 To decrease blood pressures nationwide, it is important to reduce, or at least not to increase, alcohol consumption in the Japanese population, irrespective of the type of beverage consumed. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…10, 11); alcohol consumption and physical activity increase serum HDL-C concentration, thereby conferring an antiatherogenic property [9][10][11][12][13][14][15] However, few studies have evaluated the relative importance of these factors in the variation of atherogenicity of serum lipid profile 8.10.16) We investigated the relationship of cigarette smoking, alcohol use, recreational physical activity and obesity with serum lipid atherogenicity in middle-aged Japanese men.…”
mentioning
confidence: 99%